Parallel mechanisms of Ca++ transfer across the perfused human placental cotyledon - Stulc, J; Stulcová, B; Smíd, M; Sach, I (American journal of obstetrics and gynecology, 1994)
OBJECTIVES: We dissected the paracellular and transcellular components of Ca++ transfer across the perfused human placental cotyledon and explored the nature of the transcellular component. STUDY DESIGN: Transfer of 45Ca++ and ethylenediaminetetraacetic acid labeled with chromium 51 was measured across the in vitro perfused cotyledon of the human placenta, and paracellular and transcellular components of the transfer of Ca++ were calculated from the transfer of the two tracers. RESULTS: The transcellular component of the Ca++ transfer in the maternal-fetal direction represented about one third of the total maternal-fetal transfer. It was saturable, sensitive to cyanide, and insensitive to verapamil. The transcellular component in the fetal-maternal direction was not different from zero. The in vitro transfer rates correlated well with the transfer rates estimated for the in vivo situation from data published in the literature. CONCLUSION: There is a significant active transport of Ca++ across the human placenta in the maternal-fetal direction.
Keywords: Calcium; maternofetální výměna látek; velikost orgánu; techniky in vitro; Humans; Pregnancy; verapamil; Placenta; vápník; Female; Verapamil; lidé; Sodium Cyanide; Perfusion; aktivní transport; Biological Transport, Active; Edetic Acid; ženské pohlaví; perfuze; těhotenství; In Vitro Techniques; kyanid sodný; Organ Size; Maternal-Fetal Exchange; placenta; EDTA